Using the graduated sequence instruction to combat errors in pre-calculus - Atawura, Edward Ike; Ali, Clement Ayarebilla (Journal of Mathematics and Science Teacher, 2025)
The position of developing countries on international mathematics assessments lends to a growing concern among stakeholders. The factors are multifaceted. This explanatory sequential mixed research design used the graduated sequence instruction (GSI) model to help ameliorate the situation. The researchers sampled 100 students: 50 (experimental group) received GSI and the other 50 (control group) received traditional whole-class instruction. Participants were assessed before and after the treatments. Analysis of covariance was performed to determine the effects between the groups while controlling for pre-test, sex, and age. The results indicate significant differences between the groups. However, sex and age showed no significant differences. The qualitative texts confirmed conceptual errors in traditional instruction. It was recommended that the GSI model be employed in teaching and learning basic concepts in pre-calculus.